(untitled) (Research, Society and Development, 2023)
The Cerrado is considered a biome with a high richness of plant and animal species, constituting a large part of the biodiversity, being represented by its own characteristics with landscapes of different shapes and types. This biome is made up of a diversity of species, including those present in its microfauna, such as nematodes, which are microscopic beings. Changes in soil conditions influence the abundance of nematode trophic groups. Good nutritional management helps to increase the ability of plants to establish resistance barriers, being less susceptible to damage caused by phytonematodes and other pathogens. The objective of this study was to analyze the occurrence of nematodes in the fruit trees area of the Cerrado of the Instituto Federal Goiano Campus Ceres - GO. The selected study area is located next to the Agricultural Sciences block of the Instituto Federal Goiano - Campus Ceres. The implantation of the Cerrado fruit trees occurred in 2012, with a total planted area of 60 x 60 m². The samples were collected and later taken to the soil laboratory to carry out the physical and chemical analysis, resulting in a clayey soil with good fertility. For nematode extraction, flotation-sedimentation and sieving methods were used, followed by the sample clarification technique. The presence of phytonematode was not detected in the soil samples collected in the fruit trees area; The analyzed soil showed good fertility, with base saturation (V%) above 50%; Soil organic matter can influence nematode population density.